2021
DOI: 10.1108/rpj-05-2020-0090
|View full text |Cite
|
Sign up to set email alerts
|

The effect of powder age in high speed sintering of poly(propylene)

Abstract: Purpose This study aims to demonstrate for the first time that the cheap, commodity polymer, poly(propylene), can be successfully processed using high speed sintering, and that it can be recycled several times through the process, with little to no detriment to either the polymer itself or the parts obtained. This is significant as a step towards the realisation of high speed sintering as a technology for high-volume manufacturing. Design/methodology/approach A poly(propylene) powder designed for laser sinte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Presumably, because the PET crystallises slowly, the curl was not severe enough to cause any builds to fail. This can be contrasted with Williams et al, who found that a good proportion of build failures occurred during HSS with virgin PP powder [ 25 ]. In such cases, the edges of the part area curl so heavily and protrude above the bed that the re-coater pulls them out of the powder bed surface and the manufacturing process must be aborted.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Presumably, because the PET crystallises slowly, the curl was not severe enough to cause any builds to fail. This can be contrasted with Williams et al, who found that a good proportion of build failures occurred during HSS with virgin PP powder [ 25 ]. In such cases, the edges of the part area curl so heavily and protrude above the bed that the re-coater pulls them out of the powder bed surface and the manufacturing process must be aborted.…”
Section: Resultsmentioning
confidence: 71%
“…Most of the work on HSS was conducted with PA 12 (the same as with LS of thermoplastic powders). However, the feasibility of processing various elastomers [ 20 , 21 , 22 , 23 ], polymethyl methacrylate [ 24 ] and PP [ 25 ] via HSS have also been investigated. Remarkably, Hopkinson’s team also analysed and convincingly showed the economics and scalability of HSS [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…and bonding. [164,165] The working principle of HSS is to first apply a layer of required material powder, followed by the application of a radiation absorbing material (RAM) coating in the desired shape of the object. Next, the entire workspace is heated using an infrared source.…”
Section: Research Focus and Prospects Of Bjmentioning
confidence: 99%